Sustainable Tourism Development Potential in the Improvement of Economic and Social Life Community Corridor in Bali - Wesnawa, I Gede Astra (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
This research was conducted in the Corridor Bali with the aim of (1) mapping of Bali tourism potential of the area and (2) analyze the direction of the development of tourism potential. This research uses descriptive design with the object of the research potential of tourism and socio-economic life of society corridors Bali. Subjects were community stakeholders in tourism, department of tourism, small industry related to tourism, public figures...